Epigenome–wide DNA methylation signature of plasma zinc and their mediation roles in the association of zinc with lung cancer risk. (15th August 2022) - Meng, Hua; Wei, Wei; Li, Guyanan; Fu, Ming; Wang, Chenming; Hong, Shiru; Guan, Xin; Bai, Yansen; Feng, Yue; Zhou, Yuhan; Cao, Qiang; Yuan, Fangfang; et al.
Abstract: Essential trace element zinc is associated with decreased lung cancer risk, but underlying mechanisms remain unclear. This study aimed to investigate role of DNA methylation in zinc-lung cancer association. We conducted a case-cohort study within prospective Dongfeng-Tongji cohort, including 359 incident lung cancer cases and a randomly selected sub–cohort of 1399 participants. Epigenome-wide association study (EWAS) was used to examine association of plasma zinc with DNA methylation in peripheral blood. For the zinc-related CpGs, their mediation effects on zinc-lung cancer association were assessed; their diagnostic performance for lung cancer was testified in the case-cohort study and further validated in another 126 pairs of lung cancer case-control study. We identified 28 CpGs associated with plasma zinc at P  < 1.0 × 10 −5 and seven of them (cg07077080, cg01077808, cg17749033, cg15554270, cg26125625, cg10669424, and cg15409013 annotated to GSR, CALR3, SLC16A3, PHLPP2, SLC12A8, VGLL4, and ADAMTS16, respectively) were associated with incident risk of lung cancer. Moreover, the above seven CpGs were differently methylated between 126 pairs of lung cancer and adjacent normal lung tissues and had the same directions with EWAS of zinc. They could mediate a separate 7.05%∼22.65% and a joint 29.42% of zinc-lung cancer association. Compared to using traditional factors, addition of methylation risk score exerted improved discriminations for lung cancer both in case-cohort study [area under the curve (AUC) = 0.818 vs. 0.738] and in case-control study (AUC = 0.816 vs. 0.646). Our results provide new insights for the biological role of DNA methylation in the inverse association of zinc with incident lung cancer. Graphical abstract: Image 1 Highlights: We conducted the first epigenome-wide DNA methylation analysis of plasma zinc. Plasma zinc is significantly associated with methylation levels at 28 CpGs. Zinc-associated CpGs mediate 7%∼23% of the zinc-lung cancer association. DNA methylation plays a critical role in the inverse association of zinc with lung cancer risk.